Stress Corrosion Behaviors of 316LN Stainless Steel in a Simulated PWR Primary Water Environment - Yong Huang (Materials, 2018)
The effect of the strain rate, experimental temperature, Zn content in the test solution, and prefilming time on the mechanical properties was investigated by a tensile test with a slow strain rate, at a chemical solution of 2.2 ppm Li and 1200 ppm B in a static autoclave with 8.2 MPa. The experimental parameters clearly affected the tensile properties. The surface morphology, fractograph, and cross-sectional microstructure were analyzed by scanning electron microscopy and transmission electron microscopy. The δ (elongation) and UTS (ultimate tensile strength) of the samples tested in chemical solution were obviously lower than those of the samples tested under a nitrogen atmosphere. However, in general, all samples showed a ductile fracture characteristic and an excellent tensile property in all experimental conditions. The δ and UTS were first increased with increasing Zn content, and then decreased at both conditions of 9.26 × 10−7/s and 4.63 × 10−7/s strain rates. The difference values of tensile properties at different strain rates showed fluctuations with increasing Zn content. The δ increased with both increasing experimental temperature and prefilming time. The UTS first decreased with increasing prefilming time and then increased. The Iscc (stress corrosion cracking susceptibility) decreased with an increasing strain rate, experiment temperature, and prefilming time. Many particles with polyhedrons were formed on the sample surfaces, which was attributed to corrosion in a periodical location at the sample surface. The average length of the particles decreased with increasing Zn content, but increased with both increasing experimental temperatures and prefilming time. The corresponding mechanism is also discussed in this work.